A novel single-phase hpf hybrid rectifier suitable for front-end trolleybus systems - Freitas, Luiz C. G.; Lima, Gustavo B.; Gonçalves, Flávio A. S. [UNESP]; Melo, Guilherme A. [UNESP]; Canesin, Carlos A. [UNESP]; De Freitas, Luiz C. (Institute of Electrical and Electronics Engineers (IEEE), 2009)
This paper proposal presents the development and the experimental analysis of a new single-phase hybrid rectifier structure with high power factor (PF) and low harmonic distortion of current (THDI), suitable for application in traction systems of electrical vehicles pulled by electrical motors (trolleybus), which are powered by urban distribution network. This front-end rectifier structure is capable of providing significant improvements in trolleybuses systems and in the urban distribution network costs, and efficiency. The proposed structure is composed by an ordinary single-phase diode rectifier with parallel connection of a switched converter. It is outlined that the switched converter is capable of composing the input line current waveform assuring high power factor (HPF) and low THDI, as well as ordinary front-end converter. However, the power rating of the switched converter is about 34% of the total output power, assuring robustness and reliability. Therefore, the proposed structure was named single-phase HPF hybrid rectifier. A prototype rated at 15kW was developed and analyzed in laboratory. It was found that the input line current harmonic spectrum is in accordance with the harmonic limits imposed by IEC61000-3-4. The principle of operation, the mathematical analysis, the PWM control strategy, and experimental results of a 15kW prototype are also presented in this paper. © 2009 IEEE.
Keywords: Electrical vehicles; Hybrid rectifiers; Power factor correction; Trolleybus; Urban electrical transportation systems; Electrical motors; Electrical transportation systems; Experimental analysis; Front-end converters; Harmonic limit; High power factor; Line current harmonics; Line currents; Mathematical analysis; Output power; Parallel connections; Power factor corrections; Power ratings; PWM control; Single-phase diode rectifiers; Switched converters; Traction systems; Urban distribution; Automobile electronic equipment; Automobile parts and equipment; Distributed parameter networks; Electric connectors; Electric network analysis; Electric power factor; Harmonic analysis; Power electronics; Electric rectifiers